Graphitic carbon nitride composites as electro catalysts: Applications in energy conversion/storage and sensing system. (20th October 2021) - Govindaraju, Varsha Raj; Sureshkumar, Kempahanumakkagari; Ramakrishnappa, Thippeswamy; Muralikrishna, Sreeramareddygari; Samrat, Devaramani; Krishna Pai, Ranjith; Kumar, Vanish; Vikrant, Kumar; Kim, Ki-Hyun
Abstract: The electrochemical applicabilities of graphitic carbon nitride (g-C3 N4 ) are yet confined to a degree (e.g., due possibly to an inherently low electrical conductivity) to contrast its great utility in photocatalytic applications. However, desirable electronic properties along with chemical stability can be achieved through coupling with various conducting substrates or modification of surface properties. The electrocatalytic activity of g-C3 N4 was greatly enhanced by doping of hetero atoms, alloying with conducting substrates, noble metals, and other nanostructures. As such, composites of g-C3 N4 have attracted widespread attention due to their great potential in environment and energy sectors as electro and photoelectrocatalysts. The electro catalytic applications are diverse enough to include hydrogen evolution reaction (HER), oxygen evolution reaction (OER), oxygen reduction reaction (ORR), fuel cells, supercapacitors and electro/photoelectrochemical sensors. This review presents the basic aspects of various studies on g-C3 N4 composites in electro and photoelectrochemical applications such as energy conversion reactions, storage and sensors along with a discussion of their future prospects. Graphical abstract: Diverse applications of g-C3 N4 -based electrocatalytic materials. Image 1